Assessment of hyperacusis with a newly produced Japanese version of the Khalfa hyperacusis questionnaire. (2nd September 2017) - Oishi, Naoki; Yamada, Hiroyuki; Kanzaki, Sho; Kurita, Akihiro; Takiguchi, Yoichiro; Yuge, Isamu; Asama, Yoji; Masuda, Masatsugu; Ogawa, Kaoru
Abstract: Objectives: The purpose of this study was to determine the validity and reliability of a Japanese version of the Khalfa hyperacusis questionnaire (KHQ) and proposed a threshold KHQ score for classifying hyperacusis. Methods: In total, 112 patients with hyperacusis (group A) and 103 patients without hyperacusis (group B). The patients in group A were further classified into the following subgroups: subjects with hyperacusis as their chief complaint ( n  = 26, group A1) and subjects with hyperacusis accompanied by chief complaints of tinnitus and/or hearing loss ( n  = 86, group A2). Results: The average total questionnaire score for patients in group A was 11.8 ± 9.7, which was statistically significantly higher than that of patients in group B, 5.7 ± 4.8. Cronbach's coefficients for internal consistency were high for the total score (0.92). The average total scores for groups A1 and A2 were 18.1 ± 11.1 and 9.9 ± 8.4, respectively, and the difference between the groups was statistically significant. Conclusions: We developed a Japanese version of the KHQ. It showed high reliability and validity; suggesting its usefulness in clinical practice. We propose that a total KHQ score of 16 is an appropriate cutoff for classifying hyperacusis